Efficacy of shear wave elastography for evaluating right ventricular myocardial fibrosis in monocrotaline-induced pulmonary hypertension rats. Issue 1 (July 2021) - Nakayama, Rie; Takaya, Yoichi; Nakamura, Kazufumi; Kondo, Megumi; Kobayashi, Kaoru; Ohno, Yuko; Amioka, Naofumi; Akagi, Satoshi; Yoshida, Masashi; Miyoshi, Toru; Ito, Hiroshi
Highlights: Shear wave elastography (SWE) is a novel technique for assessing tissues. Shear wave (SW) elasticity of right ventricle was higher in pulmonary hypertension. SW dispersion slope of right ventricle was lower in pulmonary hypertension. SW elasticity and dispersion slope were related to myocardial fibrosis. SWE has the potential to evaluate myocardial characteristics. Abstract: Background: Right ventricular (RV) function is important for outcomes in pulmonary hypertension. Evaluation of RV myocardial characteristics is useful to assess the disease severity. Shear wave elastography (SWE) provides information of shear wave (SW) elasticity, which is related to tissue hardness, and SW dispersion slope, which reflects tissue viscosity. This study aimed to test the hypothesis that SW elasticity is increased and SW dispersion slope is decreased in the right ventricle of monocrotaline (MCT)-induced pulmonary hypertension rats. Methods: Rats were divided into MCT-induced pulmonary hypertension group ( n = 10) and control group ( n = 10). SW elasticity and SW dispersion slope were measured on excised hearts. Myocardial fibrosis was evaluated histologically. Results: RV hypertrophy was observed in the MCT group. SW elasticity of right ventricle was higher in the MCT group than in the control group (3.5 ± 0.9 kPa vs. 2.5 ± 0.4 kPa, p < 0.01). SW dispersion slope of right ventricle was lower in the MCT group than in the control group (5.3 ± 1.7 m/s/kHz vs. 7.7 ± 1.5 m/s/kHz, p < 0.01). The fibrosis area of right ventricle was increased in MCT group compared with control group (18 ± 5% vs. 8 ± 3%, p < 0.01), and was positively related to SW elasticity and negatively related to SW dispersion slope. Conclusions: Higher SW elasticity and lower SW dispersion slope were observed in the fibrotic myocardium of right ventricle in MCT-induced pulmonary hypertension rats. SWE may have the potential to evaluate RV function by assessing myocardial characteristics.